Clinical and demographic characteristics of patients with neuro-ophthalmological disorders starting later in life (Annals of Medical Research, 2023)
Aim: To determine the demographic, etiological, and clinical features and treatment modalities of patients with neuro-ophthalmological disorders starting at a later age.Materials and Methods: We retrospectively reviewed the clinical data related to the neuro-ophthalmology patients who presented at the geriatric age at two tertiary eye care referral centers from 2004 to 2022.Results: Of the 2,127 patients who applied to the Neuro-Ophthalmology Department during this period, 162 (7.6%) were ≥ 65 years old at the time of diagnosis, and their data were analyzed. The mean age at the onset of the disease was 73.2 ± 6.7 (65–95) years, and the mean follow-up time was 1.1±0.4 (1-3) years. Non-arteritic anterior ischemic optic neuropathy (NAAION) (n=85, 52.5%), isolated cranial nerve palsies (n=28, 17.3%), and cerebral vascular disorders (CVD) (n=14, 8.6%) were the most frequent diagnosis. The most common symptoms were as follows: sudden visual loss in 79 (48.8%), diplopia in 31 (19.1%), and blurred vision in 21 (13%) cases. The most common accompanying systemic disease was hypertension (HT) and diabetes mellitus (DM) in 31 (27.4%), followed by HT in 29 (25.7%) cases. There was no accompanying systemic disease in 49 (30.2%) patients. The diagnosis of NAAION and AAION resulted in poor visual outcomes, while CVD presented with homonymous hemianopsia.Conclusion: NATION and CVD were the most common age-related neuro-ophthalmological disorders that cause visual acuity loss and a visual field defect at an advanced age. Identifying these disorders and managing the visual problems are essential to protect the patient's quality of life.
Keywords: Cerebral vascular disorders; Diagnosis; Neuro-ophthalmological diseases; Nonarteritic anterior ischemic optic neuropathy; Older age; Visual acuity